Impacts of freeway speed limit on operation speed of adjacent arterial roads - Fadi Alhomaidat (IATSS Research, 2021)
Speed limit is one of the essential factors associated with roadway safety. Spillover effect is the tendency of drivers to drive at a higher speed on relatively lower-speed non-freeway roadways after exiting higher-speed freeways. Speed studies were conducted on urban arterial roads with speed limits of 45 mph - all adjacent to freeways with speed limits of 55 mph and 70 mph. A comparison of speed differences between motorists who exited the freeway and those who were already driving on the arterial road was performed. Results showed that the mean speed and 85th percentile of passenger cars on arterials adjacent to 55 mph freeway were 47.3 and 51.1 mph, respectively, while the mean speed and 85th percentile of passenger cars on arterial adjacent to a higher speed 70 mph freeway were 49.5 and 53.4 mph, respectively. Differences in the mean speeds between vehicles exiting from freeways and vehicles already driving on the arterial road were observed at all four sites evaluated. This paper provides researchers, policymakers, and engineers with a better understanding of the effects of speed spillover on adjacent roads when determining whether to increase the speed limit on freeways.